Effects of canard configuration on the aerodynamics of blended wing body at low mach number / Zurriati Mohd Ali - Mohd Ali, Zurriati (Institute of Graduate Studies, UiTM, 2015)
The Blended Wing-Body (BWB) aircraft is an unconventional aircraft that offers the aerodynamics performance advantages compared to the conventional aircraft. This type of aircraft has a unique design where the main body is blended together with the wing that gives the additional lift of the aircraft. In contrast to the conventional aircraft, the BWB has a poor stability due to the absence of the tail. A possible solution is by using a horizontal control surface, the canard, to improve the stability of the BWB. For this purpose, a comprehensive investigation of the aerodynamic behavior of the BWB with canard is important…